The Making of a Ghetto Place-Based Policies, Labeling, and Impacts on Neighborhoods and Individuals - Yajna Govind; Jack Melbourne; Sara Signorelli; Edith Zink (Institute of Labor Economics (IZA), 2024)
Does the labeling of neighborhoods affect their outcomes? Place-based policies targeting disadvantaged areas aim to improve their conditions, but the labels they impose carry consequences of their own. In this paper, we examine Denmark's Ghetto Plan which designated public housing areas with a large share of immigrant population, high crime, and high unemployment as "ghettos", with minimal additional implications. We exploit Danish administrative data, and adopt a Difference-in-Differences approach at the neighborhood and individual level. We find that the policy led to worsening average characteristics at the neighborhood level, largely due to compositional changes driven by Danish new entrants with lower income and education levels. Following individuals affected by the policy, we find significant negative effects on their income with no discernible effects on criminal behavior. We estimate that Danes are willing to accept a 3% drop in income to move out of labeled neighborhoods. In all, the Danish ghetto policy was largely ineffective, and in some aspects, even detrimental.
Keywords: J15; J18; R23; 330; residential segregation; place-based policies; migration; neighborhood effects